Assessment of natural and anthropogenic impacts of the Irganay Hydroelectric Power Station reservoir zone on eco‐ and geosystems using remote sensing data, Dagestan, Russia - R. T. Radzhabova; L. Sh. Akhmedova (Юг России: экология, развитие, 2024)
Aim. The research and mapping of natural object dynamics using aerial and satellite imagery is one of the long‐established and actively developing fields of remote sensing and geographic research. The current phase is characterised by the wide availability of remote sensing data processing software, which offers almost unlimited possibilities for transforming and integrating datasets from different periods.Material and Methods. For the effective use of archival maps in studying territorial dynamics, two interconnected factors are critical: the date of the map’s creation and the positional accuracy of the mapped objects. The materials used in this study were TM/Landsat satellite images from the periods 2002–2017 and 2006–2014.Results. Reservoirs with a surface area of up to 60–70 km² and a volume of up to 250 million m³ increase absolute air humidity by 10–15 %. In areas with a hot climate, the impact of a reservoir on air humidity is even more pronounced.Conclusions. The anticipated significant changes in the microclimate are expected to affect the structure of agricultural production in the Irganay valley and in the villages of Maidanskoye, Untsukul, and Gimry, particularly through changes in precipitation distribution during the growing season.